Creating entrepreneurial space : talking through multi-voices, reflections on emerging debates - Higgins, David; Jones, Paul; McGowan, Pauric (Contemporary issues in entrepreneurship research ;, 2019)
Entrepreneurship is still regarded by many as in the theory building stage, which has led to some commentaries to suggest that the field is fragmented and at a nascent stage of development. Developing a critical and constructive position towards current theories, methods, assumptions and beliefs, the book seeks to question the prevailing assumptions currently dominating entrepreneurial researching and practice. The book brings together leading thinkers, practitioners and researchers in the field to draw upon new theoretical perspectives and approaches as a means of illustrating the inherently social and contextualized nature of entrepreneurial practice, and advance the manner in which we critically think about and engage with various aspects of entrepreneurial practice and development. Including a unique combination of studies that illustrate critical perspectives of current entrepreneurship research, the book covers a broad spectrum in terms of topics and approaches, as well as in terms of diversity and critique in their perspectives towards entrepreneurial practice and scholarship.